Is it safe and effective to leave Titanium Elastic Nail (TEN) tips outside the skin in pediatric femoral diaphyseal fractures? - Cemil Ertürk; Gürkan Çalışkan; Halil Büyükdoğan; Necati Doğan (Acta Medica Alanya)
Aim: In this study, we aimed to retrospectively evaluate the use of nail tips outside and under the skin in TEN (Titanium Elastic Nail) application in pediatric femur diaphyseal fractures.Patients and methods: Forty-six patients (47 fractures) who underwent TEN due to femoral diaphyseal fractures between January 2016 and July 2019 were examined retrospectively. While the patients whose TEN ends were left outside the skin were called Group 1, the patients whose TEN ends were left under the skin were called Group 2.. Age, gender, fracture side, and follow-up periods were evaluated. Clinical evaluation; hip and knee ROM (range of motion), rotational or angular deformities, pin bottoms, incision scars, infective findings; In radiological evaluation; angulation, deformity and length differences were examined on two-way radiography. Implant removal times and all complications were evaluated.Results: 21 fractures (Group 1) TEN ends were left outside the skin; In 26 fractures (Group 2), the TEN ends were left under the skin. Both groups had similar distributions in terms of age, gender and fracture sides. The follow-up period of Group 2 was significantly longer (p<0.05), but the minimum follow-up period in both groups was 9 months. There was a significant difference in the distribution of coronal and sagittal angulations in both groups (p<0.05), but all of the angulations were within acceptable limits in their age groups. Pin bottom discharge of both groups had similar distribution. (p>0.05) In terms of implant removal time, Group 1 achieved this in a shorter time compared to Group 2. (p<0.05) Union was achieved without any problems in all fractures in both groups. No notable angulation defects, rotation defects or shortness were observed in the patients. No patient developed infection in deep tissues.Conclusions: In pediatric femur diaphyseal fractures, in addition to removing the implants in a short time under outpatient clinic conditions and without the need for anesthesia by leaving the TEN ends outside the skin; leaving the implant tip outside seems to be quite advantageous, since union or angulation problems are similar to nail tips being left inside. However, nail root infection is still a serious concern; therefore, we believe that this problem can be solved with close monitoring and parental education.